KESUKSESAN APLIKASI PELAPORAN KEUANGAN DAN KINERJA ORGANISASI OPD KOTA/KABUPATEN DI PROVINSI RIAU - Gunasanti, Ursula; Fitrios, Ruhul; L, Al Azhar; Zakya, Ismon (Jurnal Agregasi, 2022)
This study aims to determine the effect of organizational culture and organizational commitment on the success of financial reporting applications/accounting information systems (AIS) and organizational performance. The population of this research is RAO (Regional Apparatus Organization) city / regency in the northern coastal area of ​​Riau Province. The sample selection used proportional stratified random sampling and obtained a total sample size of 104 OPDs and 262 respondents returned the questionnaire. The data analysis used in this research is Smart PLS. The results show that 1) organizational culture affects the success of financial reporting applications, 2) organizational culture affects organizational performance, 3) organizational commitment has no affect on the success of financial reporting applications, 4) commitment organizational has no affect on organizational performance, 5) the success of financial reporting applications affects organizational performance. The results of this study indicate the importance of developing a strong organizational culture to increase the success of financial reporting applications to support organizational performance. In addition, a strong organizational culture can directly strengthen organizational performance.